Hindsight bias. - Chia, Ti Yu. (2013)
This study aims to value the convertible bonds listed on the Stock Exchange of Singapore, using the Synthetic Approach. This study was motivated by the fact that little research has been done in this area, and the growing popularity of issuing convertible bonds as a means of raising capital. The sample for this study was drawn from the period starting January 1980 to October 1995. The sample consisted o f l l issues ofSingapore convertible bonds and 7 issues of Malaysia convertible bonds. Using the Synthetic Approach, the convertible bonds were valued separately as a straight bond and a call option on the shares of the issuing companies. The values of the straight bonds were obtained by discounting the future coupons and maturity payment, and the option part was calculated using the Black-Scholes Option Pricing Model. Other tests on the attractiveness of the convertible bonds were also conducted in this study. The results of this project revealed that the model was better at pricing convertible bonds issued by Singapore companies than Malaysia companies. In general, the model underprices Singapore issues and overprices Malaysia issues of convertible bonds. This is derived from the fact that the average percentage difference for the Singapore sample is only -4.73% as compared to 13.55% for the Malaysia sample. Additional tests involving dividends were conducted and results showed that the impact of dividends on the model was negligible as the maximum difference between models including and excluding dividends is only a mere 0.05%. In conclusion, the model is easy to apply and yet able to achieve results similar to other pricing models previously used.